the course of a invasive meningococcal disease in a patient of military age from specific prophylaxis (clinical case) - V. V. Sharabkhanov; K. V. Zhdanov; S. M. Zakharenko; N. I. Lvov; K. V. Kozlov; E. N. Koudelka; Yu. I. Lyashenko; K. S. Ivanov; Yu. I. Bulankov; A. N. Kovalenko; M. V. Yaremenko; V. A. Cheprakova; et al. (Журнал инфектологии)
Meningococcal infection is an acute infectious disease caused by Neisseria meningitidis, characterized by a polymorphism of clinical manifestations from meningococcus carriage to invasive forms. They, in turn, pose a great danger to the patient’s life, since in most cases they have a severe course with the development of complications, fulminant course and high mortality. The success of treatment of invasive meningococcal disease largely depends on the timeliness of diagnosis and the timing of treatment initiation. The article describes a clinical case of a generalized form of severe meningococcal infection with a rapidly developing infectious toxic shock, disseminated intravascular coagulation syndrome in a soldier who had previously refused specific prophylaxis. Despite the mistakes made at the prehospital stage and, accordingly, late hospitalization, this case had a favorable outcome.